Bioinformatika: Komputer, Statistika, Matematika, Biologi - Edi, Edi (STMIK TIME, 2017)
Bioinformatics is an interdisciplinary field of computer science, mathematics, statistics in solving biology-related problems. The invented DNA makes this field grow faster as scientists created database and tools to analyze it. In this article, author introduces definition of bioinformatics along with its applications as well as the development of bioinformatics in Indonesia. Literature survey is used as a research method.